24‐hour multi‐pH recording of the postprandial acid pocket and the nocturnal acid distribution at the esophagogastric junction in healthy volunteers. Issue 11 (26th August 2019) - Moonen, An; Aguilera‐Lizarraga, Javier; Bisschops, Raf; Moonen, Peter; Tack, Jan; Boeckxstaens, Guy E.
Abstract: Background: Postprandial stationary pH monitoring studies have identified the acid pocket. To what extent a similar pool of acid is present in the fasting state or at night remains however unclear. Methods: The study was performed in 9 HV without a hiatal hernia. A pH‐impedance‐pressure catheter was positioned at the Z‐line. First, the presence of the acid pocket was monitored under stationary conditions during 2 hours after ingestion of a standardized meal. Thereafter, the equipment was connected to an ambulatory monitoring device for 24‐hour recording. Results: Under stationary conditions, a postprandial acid pocket was present in 7 of the 9 HV, from 9 ± 7 minutes after meal onwards during 47 ± 8 minutes. During ambulatory 24‐hour monitoring, postprandial acid pockets emerged significantly later, but no differences in duration or position were detected. During nighttime, an acid pool was detected with its proximal border at the level of the cardia, which at later, time points gradually moved to a more distal position. This led to a gradual decrease in nocturnal acid exposure from proximal to distal, a phenomenon that was preceded by a bust of gastric contractions. Nocturnal reflux originated from the cardiac region, and was more acidic in the early compared with late nocturnal period. Conclusion: The acid pocket is present in the postprandial period under both stationary and ambulatory conditions. Of interest, at night, a pool of acid can be demonstrated which is periodically shifted more distally. This pool of acid represents the reservoir from which nocturnal reflux originates. Abstract : We demonstrated that the acid pocket is present in the postprandial period under both stationary and ambulatory conditions. Of interest, at night, a pool of acid can be demonstrated which is periodically shifted more distally. This pool of acid represents the reservoir from which nocturnal reflux originates.